The Political Texture of Islam in Southeast Asia - Justus M van der Krocf (Journal of Dharma, 1982)
On April 23, 1981. Indonesia’s Vice-President Adam Malik. speaking at the opening of the Islamic University Students’ Association in the West Java city of Bundung, expressed his concern that there were those in the country who "under the pretext of Islam" were trying to change the character and constitutional foundations of the Indonesian Republic. Criticizing what he termed the "narrow-mindedness and selfishness" of these alleged Islamic subversives, Malik reminded his audience that while under the Indonesian Constitution each citizen is "guaranteed the freedom of upholding his belief in Almighty God," such a freedom "must not be taken as an unlimited one." I He stressed the importance of Indonesia’s Pancasila ("Five Pillars"), the country’s official national ideology. Though the Pat/casita recognizes belief in God. along with nationalism, democracy, social justice, and humani- tarianism as national policy principles. many Muslims in Indonesia regard it as a secular, "man made" doctrine that cannot compete in significance and moral force with Islam’s own" Pillars of Faith."